The long-term stability of deuterated thin titanium films. (1st March 2019) - Fritzsche, H.; Ellis, B.; Patel, J.; Lang, J.
Abstract: Using neutron reflectometry, we investigated the deuterium desorption of Pd-covered Ti films that have been deuterated at 1 bar deuterium at room temperature and then exposed to air. The deuterium content was monitored continuously for the first two days. Thereafter, measurements were conducted periodically, spanning a period of up to 2 years. The films were in the thickness range of 10–300 nm and the desorption behaviour showed a strong dependence on the film thickness. The smaller the Ti film thickness the faster the Ti films desorbed the stored deuterium. Graphical abstract: Image 1 Highlights: Deuterium desorption in thin Pd-covered Ti films was monitored over 2 years The thinner the Ti films, the faster they desorb the deuterium After 2 years a 10 nm thick Ti film desorbed 80% of its originally stored deuterium After 4 days the deuterium concentration follows an exponential decay